A case study to evaluate lean product development practices in the global automotive industry. (1st January 2014) - Saunders, Tim; Gao, James; Shah, Satya
This paper describes the findings of an exploratory industrial investigation to evaluate the challenges encountered in the transformation to achieve Lean Product Development (LPD) through a case study within a multi-national automotive manufacturing company. Three specific key areas within LPD were examined in detail: (a) organisational restructuring aimed at balancing global functional engineering expertise and cross functional integration, (b) growing and maintaining technical competencies across a global product development workforce, and (c) the motivation for the separation of the in-house manufacturing divisions and subsequent integration of external specialist suppliers into the global product development process. The research examines the evolution in practices at the company since the last decades of the 20th century, through to the latest challenges in delivering global platform programmes. A comprehensive overview of related literature is also presented, which provides contextual information and justifies the selection of the key areas of focus in this study. Finally, recommendations for further research directions in this context are provided.